(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
in this article, folklore works and its teaching and its importance are interpreted today as a pedagogical problem. The works of folklore and its history are scientifically theoretical analyses of the role in the life of society and the nation and its foundations. Methodological approaches and analyzes on the use of modern technologies for teaching folklore works have been given.